Risk Assessment on Online Learning Method in Indonesian Higher Education Institution during Pandemic Covid-19 - Bayu Hari Nugroho; Sawarni Hasibuan (PT FORMOSA CENDEKIA GLOBAL, 2022)
In early 2020, the spread of the Covid-19 virus spread in Indonesia. The Indonesian government implements distance learning at all levels of education. This study aims to examine 47 risks that can disrupt the online learning process, especially in tertiary institutions. The risk matrix method consists of low risk, medium risk and high risk classifications. Of the 47 potential risks assessed, 29.78% are classified as low risk, around 63.83% are classified as medium risk, then 6.39% are classified as high risk. This study found unfulfilled numbers for student enrollment; plagiarism and bandwidth consumption as high risks in e-learning methods during the co-19 pandemic. Higher education management needs to make a strategic plan in anticipating these risks. This study provides several strategies using the 5W+1H method. The strategy is to recalculate tuition fees and payment methods to increase student enrollment, HEI management must implement regulatory policies and also apply the UPCC method to minimize plagiarism, and optimize information technology to manage bandwidth consumption.